Aktivitet i ingenmansland : En undersökning av sökbeteendet bland arbetslösa sjukskrivna - Andersson,Johan (2005)
Absenteeism due to sickness has increased during the last few years and has become a serious problem of society in Sweden. Among the sick-listed there is a group that apart from being sick are also unemployed. The aim of this paper was to study if and how the unemployed seek employment when they are sick-listed. Central questions have been if the unemployed seek employment while they are sick-listed? To what extent do they seek employment? Which methods do they use and what demands do they make of their prospective jobs? The survey was based on a quantitative method and the answers that 100 unemployed sick-listed in the northwest of Skåne, Sweden gave to questionnaires. The result was analysed using a bivariate analysis in order to find patterns or obvious differences. The result showed that more than half (60 percent) of the people in the survey group used up to an hour or more per week to search for or apply for work. Approximately a quarter (23 percent) had formally applied for one or more jobs during a month. The most common method used to search for jobs was newspaper ads (43 percent). The result also showed that 38 percent of the 60 percent that were actively seeking employment were willing to accept a wage that was equal to or less than the current compensation (sickness benefit) they were receiving from the Swedish Social Insurance Administration (försäkringskassan).
Keywords: arbetslösa; arbetslöshet; sjukskrivningar; söka arbete; Sociology of labour, sociology of enterprise; Arbetslivssociologi, företagssociologi; Social problems and welfare, national insurance; Sociala problem, social välfärd, socialförsäkring